Synthesis, DFT, electrochemical, biological and DNA-interaction studies of a novel copper(II) complex of salicylic acid and N-tosyl substituted benzimidazole - Rashid, N; Kiran, A; Ahmad, I; Ashraf, Z; Yamin, BM; Rafiq, M (Taylor & Francis Ltd, 2024)
Indexed by WOS/SCOPUS/ERA